UPAYA PENINGKATAN PENGETAHUAN IBU HAMIL DALAM PENCEGAHAN STUNTING DI DESA TERATAK, BATUKLIANG UTARA - Putri, Fitria Agustina Budiono; Permadi, Dena Indiarto; Aninfento, Deanaldo Setiawan; Muhidayani, Respi Eka Septi; Surachman, Dyah Fortuna; Ijah, Uswatun; Mustaqrobin, Achmad Sajidan; Muslihatun, Muslihatun; Hadi, Irfan Zikrul; Hannisa, Pina; Hayati, Hayati (Universitas Mataram, 2024)
Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the first 1000 days of life. This condition is the result of the child's nutritional needs not being met, which results in the child's height becoming very short. Currently, there are still cases of stunting in Teratak Village, even though this village is one of the areas with fisheries and livestock natural resource commodities. This can occur due to low public knowledge of the importance of adequate nutrition in preventing stunting. Therefore, increasing pregnant women's knowledge of healthy food choices is one of the efforts that can be made to prevent stunting. This effort takes the form of providing health education or nutrition education in the form of outreach activities. This research aims to determine the increase in knowledge of pregnant women regarding stunting prevention in the first 1000 days of a child's life. The method used was education for pregnant women in Teratak Village with a total of 15 people. To test the effectiveness of this extension, pre-test and post-test methods were used with a qualitative approach. The results of this outreach show that there is an increase in pregnant women's knowledge of stunting prevention in Teratak Village. This increase can be seen from the increase in the mean value which rose from 68.7 before the counseling to 87.3 after the counseling was carried out.